BABI, ANJING, DAN DARAH: Konstruksi Kebudayaan Kuliner Non-Halal - Koeswinarno Koeswinarno; Zakiyah Zakiyah (Jurnal Sosiologi Agama, 2022)
The existence of non halal food in Javanese society especially in Surakarta regency was a phenonema that needs to be studied. This is because the number of consumtion rate on this non halal food namely pork, dog and blood, was relatively high in this area. In addition, the tradition of consuming those non halal food is closely related with the “culture” and the surrounded social construction. Even, recently the non halal food becomes a trending topic in the social media. This article was written based on the qualitative research condudted in Surakarta. Data were collected using interview, observation and documentary study, then those collected data were analysed using a framework offered by Spreadly, as it said that culture on the retieved knowledge, then it was used to interprete such experience and created social behaviour. Findings of this research depicts that those non halal food have not fully accepted by the community in Surakarta, in which the majority of them are Moslem. However, those three kinds of food are available on several resaturants with the symbolic name such as B1 and B2. Furthermore, those three types of food have different position in the society; for instance, dog has long history and it is always nurtured by the society. Besides, pork is always sold by non-Moslem seller, in contrast dog and blood are sold by non-Moslem and Moslem seller, although Moslem seller did not consume them. Moreover, the existence on non halal food become a debate in the society and on the social media like Youtube.